2011
DOI: 10.1002/elan.201000404
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescence Aptamer Biosensor for Detection of Thrombin Based on CdS QDs/ACNTs Electrode

Abstract: A label-free ECL aptamer biosensor based on CdS QDs/ACNTs electrode for the sensitive detection of thrombin was fabricated. CdS QDs and Chitosan (CTS) complex films were coated and filled the tubes of ACNTs by carrying out electrodeposition reaction of CTS-CdS QDs on ACNTs electrode, the resulting electrode showed high ECL intensity and good biocompatibility. After aptamer was bound to the film via glutaric dialdehyde, the modified electrode could be used as an ECL aptamer sensor for the thrombin detection. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…He et al also fabricated a label-free ECL aptamer biosensor based on CdS QD-carbon nanotube electrodes for the sensitive detection of thrombin. 83 After thrombin recognition on the aptamer modified QDs electrode, an obvious decrease in ECL signal was obtained. In addition, it has been found that the ECL of CdTe QDs displayed a size-dependent property (see Fig.…”
Section: Electrochemical and Electrochemiluminescence Sensorsmentioning
confidence: 99%
“…He et al also fabricated a label-free ECL aptamer biosensor based on CdS QD-carbon nanotube electrodes for the sensitive detection of thrombin. 83 After thrombin recognition on the aptamer modified QDs electrode, an obvious decrease in ECL signal was obtained. In addition, it has been found that the ECL of CdTe QDs displayed a size-dependent property (see Fig.…”
Section: Electrochemical and Electrochemiluminescence Sensorsmentioning
confidence: 99%
“…Therefore, it can be concluded that the obvious ECL decrease for thrombin solution was mostly attributed to the right recognition of aptamer to target protein. We think that the decrease in the controlling experiments came from the non-special adsorption onto electrode surface, and the adsorbed materials then acted as the electronic transfer blocker and decreased ECL intensity [46].…”
Section: The Sensitivity and Selectivity Evaluation For The Ecl Biosementioning
confidence: 99%
“…For example, Zhu’s group developed a series of aptasensors with the QDs ECL as the signal transduction for the detection of lysozyme, ATP and thrombin [ 58 , 59 , 60 ]. Aptasensors detecting lysozyme and ATP were built with the specific affinity between aptamer and target, on the basis of Watson–Crick base pairing.…”
Section: Aptamer-modified Qds For Optical Detectionmentioning
confidence: 99%
“…Aptasensors detecting lysozyme and ATP were built with the specific affinity between aptamer and target, on the basis of Watson–Crick base pairing. Taking lysozyme detection for example [ 60 ], thiolated anti-lysozyme aptamer were modified onto the pretreated Au electrode via an Au-S bond, and then incubated with lysozyme solution to form the aptamer-lysozyme bioaffinity complexes. The free aptamer were hybridized with biotin modified complementary DNA (biotin-cDNA) oligonucleotides.…”
Section: Aptamer-modified Qds For Optical Detectionmentioning
confidence: 99%